PENGOLAHAN MINYAK JELANTAH UNTUK BAHAN DASAR PEMBUATAN SABUN CUCI PADA IBU-IBU RUMAH TANGGA - Nurfajriah; Sari, Santika; Anggraini, Silvia; Zidane, Mohammad; Fitriani, Alyssa; Ad’hania, Faizha; Farhan Inarta, Muhammad (Universitas Kadiri, 2024)
Used cooking oil is a serious problem for the environment. It is expected that its management can be regulated properly. People in Kampung Pulo do not know well about cooking oil management. The repeated use of cooking oil is in fact bad for health. Through this program, it is hoped that the community can find out how to process used cooking oil into soap economically. The method of implementing the activity begins with the problem discussion stage, socialization of the dangers of used cooking oil, soap making training, and activity evaluation. The results of the activity obtained that the community can know insights related to the dangers of used cooking oil well and its processing into laundry soap that can be used in household activities. It is hoped that the implementation of the program can be sustainable and even generate income for the community through soap products that have selling value